Про методику консервації і реставрації камінних будівельних залишків Ольвії - Бєляєв, О.С.; Кудренко, А.І. (Археологія, 1994)
У статті розглядаються нові методи, технологія консервації і реставрації будівельних залишків Ольвії. В статье приводится краткий анализ различных методик и свойств консервирующих материалов, которые использовались при реставрации каменных строительных остатков античного города Ольвии. Подробно описываются технология и консерванты, разработанные специально для Ольвии на основе изучения ее природы, климатических условий, особенностей строительного камня. Авторы приходят к выводу о необходимости проведения консервации памятника сразу же после его открытия археологами. Обосновывается необходимость сочетания различных приемов консервации и реставрации даже на одном объекте, исходя из его состояния. The paper presents a short analysis of various procedures and perl tes of preserving materials which were used in restoration of stone building remains of antique town of Olbia. The procedure and preserving, materia Is developed purposefully for Olbia with allowance for its nature, climatic conditions, properties of building stone are described in detail. The authors come to the conclusion that the relic discovered by archaeologists should be subjected to the preservation procedure immediately after Us discovery. Proceeding from the stale of the object in question, it may be necessary to combine different ways of preservation and restoration even for the same object.